Peran Pemimpin Nonformal dalam Pelaksanaan Pembangunan di Desa Kayuangin Kecamatan Malunda Sulawesi Barat - Kartina, Mutiara; Idrus, Idham Irwansyah (Research Agency for Humanity and Urban, 2023)
This study aims to determine the role of non-formal leaders in implementing development in Kayuangin Village and to determine the relationship between non-formal leaders with formal leaders and the community in implementing development in Kayuangin Village. In order to achieve this goal, a qualitative research method was adopted which was analyzed and written descriptively. Data collection techniques were carried out by means of observation, interviews, and reviewing the documentation. The subjects in this study were determined deliberately, namely 15 informants. The data that has been obtained is then analyzed and interpreted based on relevant theories and research results. The results of the study show that non-formal leaders in Kayuangin Village have an important role in implementing village development. These roles are non-formal leaders participating in development planning, participating in village development decision-making processes, participating in village development implementation, inviting the community to participate in development, and playing a role in dealing with problems that arise in society. The relationship between non-formal leaders and non-formal leaders in the implementation of village development is considered not good because of the lack of synergy between the two. While the relationship between non-formal leaders and the people of Kayuangin Village is very good, it can be seen from the closeness and level of community trust in non-formal leaders.